Efektifitas Konsumsi Labu Siam terhadap Penurunan Kejadian Konstipasi pada Ibu Hamil di Puskesmas Lebak Gedong - Wahyuni, Nur Ismi; Any, Eka Nurmedia Vistari; Nursholihati, Hana; Sulistia, Egawati; Sunarti, Ida; Adiani, Heli (Universitas Malahayati, 2025)
ABSTRACT Cases of constipation found at the Lebak Gedong Health Center, data was obtained as much as 8.9% of all pregnant women in the last month, namely 39 pregnant women complained of difficulty defecating. At the Health Center, only counseling was given about a high-fiber diet and pregnancy exercises had been carried out but were not carried out optimally. So by finding this case the author is interested in knowing the effectiveness of chayote consumption on reducing the incidence of constipation in pregnant women at the Lebak Gedong Health Center in 2024. Objective to determine the effectiveness of chayote consumption on reducing the incidence of constipation in pregnant women at the Lebak Gedong Health Center in 2024. This study uses a Quasy Experimental research design with a pre-test and post-test, namely by using two groups. At the beginning of the examination, an intervention was given for group 1 which was included in the severe constipation category, an intervention was given by giving 100gr/day of chayote and group 2 which was included in the mild constipation category as a control, then a re-examination of the incidence of constipation was carried out after 15 days of intervention (post). There is a significant difference between chayote consumption. And there is a difference in the average difference between the pre-test and post-test of each group. There is an average difference of 5.13 where the Experiment consumption is higher than the average control group. Keywords: Chayote, Constipation, Pregnant Women, Lebak Gedong ABSTRAK Kasus konstipasi yang terdapat di Puskesmas Lebak Gedong, diperoleh data sebanyak 8,9% dalam keseluruhan ibu hamil dalam sebulan terakhir yaitu 39 orang ibu hamil mengeluh susah buang air besar. Di Puskesmas hanya dilakukan penyuluhan tentang diet tinggi serat dan sudah dilakukan senam hamil namun dilakukan belum maksimal. Sehingga dengan menemukan kasus ini penulis tertarik untuk mengetahui efektivitas konsumsi labu siam terhadap penurunan kejadian konstipasi pada ibu hamil di Puskesmas Lebak Gedong tahun 2024. Tujuan untuk mengetahui efektifitas konsumsi konsumsi labu siam terhadap penurunan kejadian konstipasi pada ibu hamil di Puskesmas Lebak Gedong tahun 2024. Penelitian ini menggunakan rancangan penelitian Quasy Eksperimental dengan pre test and post testyaitu dengan menggunakan dua kelompok. Pada awal dilakukan pemeriksaan, kemudian diberikan intervensi untuk kelompok 1 dengan pemberian 100gr/hari labu siam dan kelompok 2 yang masuk dalam kategori konstipasi ringan sebagai kontrol, kemudian dilakukan pemeriksaan kembali kejadian konstipasi setelah 15 hari intervensi (post). Ada perbedaan bermakna antara konsumsi labu siam. Dan ada perbedaan dari selisih rata-rata antara pre test dan post tes masing-masing kelompok. Ada selisih rata-rata sebesar 5,13 dimana konsumsi Eksperimen lebih tinggi dibandingkan rata-rata kelompok kontrol. Kata Kunci: Labu Siam, Konstipasi, Ibu Hamil, Lebak Gedong